Cell polarity proteins and spermatogenesis. (November 2016) - Gao, Ying; Xiao, Xiang; Lui, Wing-yee; Lee, Will M.; Mruk, Dolores; Cheng, C. Yan
Abstract: When the cross-section of a seminiferous tubule from an adult rat testes is examined microscopically, Sertoli cells and germ cells in the seminiferous epithelium are notably polarized cells. For instance, Sertoli cell nuclei are found near the basement membrane. On the other hand, tight junction (TJ), basal ectoplasmic specialization (basal ES, a testis-specific actin-rich anchoring junction), gap junction (GJ) and desmosome that constitute the blood-testis barrier (BTB) are also located near the basement membrane. The BTB, in turn, divides the epithelium into the basal and the adluminal (apical) compartments. Within the epithelium, undifferentiated spermatogonia and preleptotene spermatocytes restrictively reside in the basal compartment whereas spermatocytes and post-meiotic spermatids reside in the adluminal compartment. Furthermore, the heads of elongating/elongated spermatids point toward the basement membrane with their elongating tails toward the tubule lumen. However, the involvement of polarity proteins in this unique cellular organization, in particular the underlying molecular mechanism(s) by which polarity proteins confer cellular polarity in the seminiferous epithelium is virtually unknown until recent years. Herein, we discuss latest findings regarding the role of different polarity protein complexes or modules and how these protein complexes are working in concert to modulate Sertoli cell and spermatid polarity. These findings also illustrate polarity proteins exert their effects through the actin-based cytoskeleton mediated by actin binding and regulatory proteins, which in turn modulate adhesion protein complexes at the cell–cell interface since TJ, basal ES and GJ utilize F-actin for attachment. We also propose a hypothetical model which illustrates the antagonistic effects of these polarity proteins. This in turn provides a unique mechanism to modulate junction remodeling in the testis to support germ cell transport across the epithelium in particular the BTB during the epithelial cycle of spermatogenesis.